Inland Water Transport and Urban Mobility in Ikorodu-Ebutte Ero Route, Lagos, Nigeria - Usman Bolaji Abdulkadir; Animashaun Kikelomo Halimat (Department of Geography Education, University of Jember, 2020)
Lagos city has abundant navigable inland waterways which if fully harnessed would help minimise road traffic congestion, pollution and provide low cost means of long distance travel within the city. This study examines inland water transport services on Lagos lagoon focusing on Ikorodu-Ebutte Ero route. Primary data were obtained using structured questionnaires. While, secondary data were sourced from relevant government and private agencies. Data were analysed using descriptive techniques including frequency counts, tables and graphs. The results revealed an inadequate provision of terminal facilities and vessels in the area. It was also found that most (67.3%) of the trips via water transport in the were mainly for work purpose. In addition, low patronage was observed and it was found to be mostly due to comparatively high cost of fares and passenger safety concerns, as indicated by 67.4% and 58.7% of the respondents respectively. Furthermore, high income earners where found to patronise this mode than low income earners. The high frequency of use of water transport by the respondents (71.3% travel by water every day) indicates that, this mode has great potential of being widely adopted, if greater attention is given to its development by both the government and private sector. There is, therefore, a need for more investment in water transportation in the area through the provision of modern infrastructure and vessels. Keywords: urban mobility; inland waterways; transport services; sustainable transportation; integrated transport. Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License